(untitled) (Nigerian Journal of Technology, 2018)
This study is focused on adapting a pair-loader hydraulic ram for use as a drawbar hydraulic dynamometer for field tests and presenting simulative views in 3D. The ram pressure unit consists of a cylinder, piston and push rod with the hydraulic cylinder having a capacity of 26.7kN draft was used. The maximum length of ram is 540mm, diameter of piston is 80mm, and diameter of cylinder is 120mm. A hand held pressure gauge was used with maximum range capacity of 11N/mm2. The transmission line was made of a high pressure oil rubber hose, 2.75m long, and hydraulic adaptors were used to connect the oil tube to the cylinder and the pressure measuring gauge. Hydraulic dynamometers using calibrated pressure gauge indicator was adapted to measure heavy draft loads. It can be used to determine the draft, drawbar pull and travel reduction (slip) of a tractor with implement in operation and when not in operation. A field test carried out showed that at any given drawbar pull, the slippage increased with increase in draft (drawbar pull). http://dx.doi.org/10.4314/njt.v37i2.30